Parameter dependence of ELM loss reduction by magnetic perturbations at low pedestal density and collisionality in ASDEX upgrade. (17th March 2017) - Leuthold, N; Suttrop, W; Fischer, R; Kappatou, A; Kirk, A; McDermott, R; Mlynek, A; Valovič, M; Willensdorfer, M
Abstract: ELM mitigation by magnetic perturbations is studied at low pedestal collisionalities down to ITER-like values ( ν e, PED * = 0.1 ) in ASDEX Upgrade. A comprehensive database of ELM energy losses for varying plasma density, heating power, edge safety factor and magnetic perturbation structure has been assembled to investigate parameter dependencies of ELM mitigation. It is found that magnetic perturbations with a toroidal mode number n = 2 can reduce the ELM energy loss normalized to the energy stored in the plasma pedestal from about 30% to less than 5%, i.e. by a factor of six, below an electron pedestal collisionality of ν e, PED * = 0.4 . At this level of ELM mitigation a significant reduction of the pedestal pressure and, therefore, global plasma confinement occurs. This pedestal pressure reduction is mostly due to a reduction of plasma density, the so-called 'pump-out' effect. Refueling by neutral beams and in particular by pellet injection is possible and can re-establish confinement, however, the ELM energy loss increases as well with increasing density.